Analisis Sistem Bagi Hasil Kapal tangkapan Ikan di Pelabuhan Samudra Kutaraja La,pulo Kota Banda Aceh - Muhammad Aulia Fadhil; Elly Susanti; Otto Nur Abdullah (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
The development of the fisheries sector is one of the development priorities in Aceh Province so that it can have a positive impact on economic development in general. There are 2 groups of fishermen in carrying out capture fisheries production in Banda Aceh, namely the owner fisherman group and the cultivating fisherman group. ABK contained in the ship size 30-50 GT an average of 10 people and 50-80 GT as many as 26 people. The process of sharing fishery products shows that the profit sharing system seems to have been in accordance with the fishermen's sense of justice, namely that they have met the minimum criteria that must be obtained by each party. However, if it is analyzed more deeply based on the law on fishery product sharing, then this will appear to deviate far from the rules and sense of justice. So it is necessary to do an analysis of the system for the results of fishing vessels in the fishing port of Samudra Kutaraja Lampulo, Banda Aceh City. The size of the share of capital owners, sea captains and crew members (ABK) is highly dependent on the number of crew members used. Therefore, the study was conducted on ships with a size of 30-50 GT and ships of 50-80 GT which have a large number of crew members.This study aims to find out how the profit-sharing system that applies at the Ocean Kutaraja Lampulo fishing port, Banda Aceh city to ships with sizes of 30-50 GT and 50-80 GT and see the differences in the comparison of the fishery product sharing system applied to the established fishery product sharing system. in law no. 16 of 1964 concerning Fishery Revenue Sharing. The objects in this study are the ship owner, bench tauke, ship captain, and ship crew. while the scope is a boat profit sharing system between fishermen who own the ship, and fishermen working at the Kutaraja Lampulo Ocean Fishing Port, Banda Aceh. The type of data used is primary data obtained based on field observations through direct interviews with ship owners, ship toke, bench toke, ship captain and ship crew. Using a descriptive analysis model to determine the profit-sharing system for fishing at the Kutaraja Lampulo Ocean Fishery Port, Banda Aceh. Based on the research that has been done, it can be concluded as follows. The results obtained in the field regarding the revenue sharing system, the results obtained for each ship in the Prikanan Samudra Kutaraja Port are different. The distribution system for the results is not written but only in the form of an agreement between the Ship Owner, Bench Owner, Ship Captain and ABK. The profit sharing system for vessels measuring 30-50 GT and vessels measuring 50 -80 GT using purse seine fishing gear at the Samudra Kutaraja Port, Lampulo, Banda Aceh City, was obtained from a carefully made agreement between the owner fishermen and the working fishermen. The average distribution of ships size 30-50 GT for Ship Tauke 52%. Bench Tauke by 9%, captain of the ship by 12% and crew by 29%. Then - the average distribution of ships size 50 – 80 GT for Ship Tauke is 56%, Bench Tauke is 6%, Ship captain is 8% and ABK is 30%.The profit-sharing system for fishing vessels of size 30-50 GT applies a profit-sharing system according to the fishery product-sharing law of 1964. Meanwhile, vessels of size 50-80 GT apply that which is not in accordance with the fish-sharing law of 1964.